2011
DOI: 10.1016/j.biosystemseng.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of bending load capacity of timber beams using a finite element method simulation of knots and grain deviation

Abstract: A finite element model was used to simulate timber beams with defects and predict their maximum load in bending. Taking into account the elastoplastic constitutive law of timber, the prediction of fracture load gives information about the mechanisms of timber failure, particularly with regard to the influence of knots, and their local grain deviation, on the fracture. A finite element model was constructed using the ANSYS element Plane42 in a plane stress 2D-analysis, which equates thickness to the width of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 9 publications
0
26
0
1
Order By: Relevance
“…Several studies have already shown that mean grain angle is correlated to boards' mechanical properties (Pope et al 2005, Brännström et al 2008. Baño et al (2011) also showed that the association of slope of grain and nodosity measurements in a finite element model conducts to a high correlation between experimental and predicted bending strength (R 2 = 0.88). The consideration of the slope of grain appears to be effective, but finite element method is not industrially applicable because of the computational time.…”
Section: Strength Grading Technologiesmentioning
confidence: 90%
“…Several studies have already shown that mean grain angle is correlated to boards' mechanical properties (Pope et al 2005, Brännström et al 2008. Baño et al (2011) also showed that the association of slope of grain and nodosity measurements in a finite element model conducts to a high correlation between experimental and predicted bending strength (R 2 = 0.88). The consideration of the slope of grain appears to be effective, but finite element method is not industrially applicable because of the computational time.…”
Section: Strength Grading Technologiesmentioning
confidence: 90%
“…The traditional stitching 5-purlin beam is shown in Fig.1. [1,2,3,4,5,6,7,8]. But the connecting conformation and the wood material were all different from those of Chinese stitching timber beams.…”
Section: Introductionmentioning
confidence: 86%
“…One of the first papers that considered simultaneously wooden structures and calculation by FEM in rural constructions is that of Wright and Manbeck (1992). Other groups that have worked on this subject are those leaded by Gebremedhin (Cabrero and Gebremedhin, 2009), Lam (He et al, 2001), Gupta (van de Lindt et al, 2009) or Guaita (Baño et al, 2011). FEM has been used in studying greenhouse structures, analysing both the support elements and flexible plastic coverings or the foundations (their special problem of being on traction).…”
Section: Finite Element Methods In Buildings and Infrastructures Areasmentioning
confidence: 99%